Operative Time Learning Curve for an Image-Free Robotic Arm Assisted Total Knee Arthroplasty: A Cumulative Sum Analysis - Cale A. Pagan, MD; Theofilos Karasavvidis, MD; Breana Siljander, MD; Eytan M. Debbi, MD, PhD; Charles A. DeCook, MD; Jonathan Vigdorchik, MD (Arthroplasty Today)
Background: Robotic arm assisted total knee arthroplasty (RA-TKA) aims to improve accuracy in bone resection, implant positioning, and joint alignment compared to manual TKA (M-TKA). However, the learning curve of RA-TKA can disrupt operating room efficiency, increase complications, and raise costs. This study examines the operative time learning curve of RA-TKA using a single robotic system. Methods: The study analyzed the first 80 RA-TKA and the last 80 M-TKA cases performed by a single surgeon using the VELYS robotic system after transitioning from M-TKA. Cases were subdivided into groups of 20 and compared to M-TKA cases. A cumulative summation analysis identified the learning curve phases. Results: Three phases were identified: Phase 1 (initial learning, cases 1-9), Phase 2 (increased competence, plateau from cases 10-52), and Phase 3 (post-learning, optimized performance from cases 53-80). Mean surgical time for RA-TKA was 42.4 ± 8.7 minutes, compared to 35.3 ± 7.0 minutes for M-TKA (P < .001). Early RA-TKA cases (1-20) had significantly longer times than late RA-TKA cases (61-80) and M-TKA cases (P < .05). Late RA-TKA times were comparable to M-TKA (P = .06). Conclusions: RA-TKA is an enabling surgical tool that can be integrated efficiently into a surgical workflow with a rapid learning curve of 9 cases.